Mnenja učiteljev o izbiri in rabi učbenikov za pouk slovenščine - Ulaga, Karmen (K. Ulaga, 2015)
V magistrski nalogi smo preučevali mnenja učiteljev o izbiri in rabi učbenikov za pouk slovenščine. Empirični del naloge temelji predvsem na iskanju razlik med učitelji razrednega pouka, pri čemer smo jih opozorili, da nas zanimajo samo učbeniki za pouk slovenščine, in med učitelji slovenščine na predmetni stopnji. Razlike med mnenji učiteljev smo iskali glede na prioritete pri načrtovanju pouka slovenščine, glede na način izbiranja učbenikov za pouk slovenščine, glede na samo izbiro in na ustreznost učbenika, ki ga uporabljajo, raziskovali smo razlike v mnenju o pestrosti učbenikov na trgu in na koncu smo iskali zanje pomembne lastnosti kvalitetnega učbenika. Zanimale pa so nas še določene povezave med odgovori. Za pridobivanje odgovorov smo uporabili anketni vprašalnik, ki smo ga razdelili po osnovnih šolah med učitelje razrednega pouka in učitelje slovenščine ob koncu šolskega leta 2013/2014. Ugotovili smo, da se pri več odgovorih kažejo statistično značilne razlike med učitelji razrednega pouka in učitelji slovenščine. Učitelji razrednega pouka načrtujejo pouk slovenščine na podlagi intuicije in učnega načrta v večji meri kot učitelji slovenščine. Učitelji razrednega pouka pogosteje izberejo učbenik znotraj kolektiva, medtem ko učitelji slovenščine učbenik izberejo sami. Učitelji razrednega pouka so tudi bolj zadovoljni z didaktično ustreznostjo učbenika kot učitelji slovenščine. Nekaj razlik se pokaže tudi pri opredeljevanju kvalitetnega učbenika. The master's thesis examines teachers' opinions on the selection and use of the Slovene language textbooks. The empirical part of the paper focuses on the examination of differences in opinion regarding the Slovene language textbooks between the class teachers teaching the Slovene language and the subject teachers of the Slovene language it should be noted, that the class teachers involved in the research have been notified to focus merely on the Slovene language textbooks. The thesis examines how the teachers' opinions regarding the Slovene language textbooks differ in respect of the priorities in educational planning, the manner of selection, the selection and adequacy of the Slovene language textbooks in use. Furthermore, the thesis looks into different perspectives regarding the variety of the Slovene language textbooks on the market and surveys the important features of a high-quality textbook. The correlations between the teachers' answers were reviewed. For the purpose of this reasearch, a survey questionnaire was sent out to the class teachers teaching the Slovene language and the Slovene language subject teachers at the end of the academic school year 2013/2014. The evaluation of the questionnaire points out statistically significant differences in the answers provided by the class teachers teaching the Slovene language and those provided by the Slovene language subject teachers. The study findings indicate that the class teachers teaching the Slovene language plan the lessons based on their intuition and the curriculum to a greater extent than the Slovene language subject teachers. The class teachers teaching the Slovene language select the textbook jointly in professional team, whereas the Slovene language subject teachers tend to make a selection of the textbook based on their personal judgement. The class teachers teaching the Slovene language are more satisfied with didactic adequacy of the textbook than the Slovene language subject teachers. The findings also reveal the discrepancies between the definitions of a high-quality textbook.